DETERMINAN ROA, DER DAN NPM TERHADAP HARGA SAHAM PERUSAHAAN TEKNOLOGI DENGAN TOTAL ASET SEBAGAI VARIABEL KONTROL DI BURSA EFEK INDONESIA - Filipus Argentano Guntur Suryaputra (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to analyze ROA, DER, NPM and Company Size as control variables for the Stock Price of Technology companies listed on the Indonesia Stock Exchange. Stock Price is a very important element in showing the value of the company and also the return on investment. The analysis method used was multiple regression, with samples during the 2019-2022 period. The results of the study show that ROA has a positive and significant effect on the Stock Price, showing that technology companies with high profits tend to have excellent corporate value in the eyes of investors. This finding provides important insights for investors in considering investing in technology companies. Technology companies should consider how in the future to earn profits not only to expand market share.